A bibliometric analysis on 'fertility rate' research trends - Nagaratnam , Shalini; Ebrahim, Nader Ale; Habibullah, Muzafar Shah (2016)
The systematic literature search on the fertility rate was performed on articles from the Web of Science compiled by the Institute of Scientific Information (ISI) to provide major publication characteristics. All articles related to Fertility from year 1980 to 2011 were analyzed with the bibliometric approach using non-parametrics techniques. Total Citation, Citation per year and Cited References were significantly different between the 80’s, 90’s and 2000’s, with more than a 100% increase in the number of publication. The association between number of authors and citation per year were significantly weak. Number of publication in a journal posed a poor negative association with the citation per year. Similarity between Authors Keyword and KeyWords Plus® do not promote the increase in citation per year. The author’s affiliation and country of publication would be an interesting exploration for future fertility research. The bibiliometric analyses on Fertility is rather new and vital, as the key finding will provide researchers guidance in the literature search and future publication.